REFERENCE ON THERMOPHYSICAL PROPERTIES: DENSITY AND VISCOSITY OF WATER FOR ATMOSPHERIC PRESSURE - Elin Yusibani; Aprina Aprina; Teuku Khairuman (Jurnal Natural, 2016)
A reference on thermophysical properties, density and viscosity, for water at atmospheric pressure has been developed in MS Excel (as a macros). Patterson’s density equations and Kestin’s viscosity equations have been chosen as a basic equation in the VBA programming as a user-defined function. These results have been compared with REFPROF as a wellknow standart reference